Using Semantic Web for Selection of Web Services with QoS - Nakamura, Luis H. V.; Estrella, Julio C.; Santana, Marcos J.; Santana, Regina H. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
This paper introduces a module named UDOnt-Q (Universal Discovery with Ontology and QoS) that uses the Semantic Web and an Ontology based on Service Level Agreements (SLA) and attributes of Quality of Service (QoS). In order to classify and select Web Services without drastic changes in the standard Web Service architecture, two semantic algorithms were developed and included in the module. At the end, a performance evaluation was executed to compare their performance in different settings, trying to identify an efficient way to promote the selection of Web Services.